Examining the position of virtue ethics in normative ethics - مرتضی bakhshi golsefidi; mahmod namazi (اخلاق وحیانی)
Virtue ethics is known as one of the three branches of normative ethics, but some moral philosophers are not in favor of an independent position for it in normative ethics. The question of the present article is, what is position of virtue ethics in normative ethics researches? Are the arguments of those who assert the independence of virtue ethics in front of other competitors, i.e. duty-oriented and utilitarianism, without problems? What is the proposed solution? The collection of data in this article is a library, and it explains the questions and answers them with a descriptive and analytical method. Those who believe in virtue ethics have different interpretations for virtue ethics, the virtue of the moral subject is common in all of them. The reasons for turning to the ethics of virtue are numerous and mostly refer to the weak points of competing theories. Investigations show that there are problems with the interpretations of virtue ethics, and the arguments for approaching it can be undermined. The result is that although virtue ethics does not have an independent position in normative ethics, the logical concerns of those who adhere to virtue ethics can be solved by the theory of divine proximity